Preparedness for Zika virus testing in the World Health Organization Western Pacific Region - Raynal C Squires; Frank Konings; WHO Regional Office for the Western Pacific Zika Incident Management Team (World Health Organization Regional Office for the Western Pacific, 2016)
On 1 February 2016, the World Health Organization (WHO) declared that clusters of microcephaly cases and other neurological disorders occurring in Zika virus (ZIKV)-affected areas constituted a public health emergency of international concern. Increased surveillance of the virus, including the requirement for laboratory confirmation of infection, was recommended. The WHO Regional Office for the Western Pacific therefore initiated a rapid survey among national-level public health laboratories in 19 countries and areas to determine regional capacity for ZIKV detection. The survey indicated that 16/19 (84%) countries had capacity for molecular detection of ZIKV while others facilitated testing through referral. These results suggest that robust laboratory capacity is in place to support ZIKV surveillance in the Western Pacific Region.